Beyond Language Barriers: How Translanguaging Shapes Pedagogical Practice and Students’ Identity in Japanese Higher Education - Wiryani, Roossita Suci; Luciana, Luciana; Prasatyo, Bayu Andika (Jurnal Pendidikan Progresif, 2025)
Beyond Language Barriers: How Translanguaging Shapes Pedagogical Practice and Students’ Identity In Japanese Higher Education. Objective: This research addresses the critical challenge international students face in English-Medium Instruction (EMI) environments regarding the construction of conceptual knowledge and academic access. Drawing upon Social Constructivism, this study reframes translanguaging not as a linguistic deficit but as a pedagogical resource that supports student agency. The primary aim is to investigate the perceptions and functions of translanguaging among Indonesian undergraduate students in Tokyo, Japan, and to explore its connection to effective meaning-making and academic integration within a superdiverse educational context. Methods: This research employs a qualitative narrative inquiry approach, which is well-suited to capturing students’ lived experiences and providing in-depth insights into how they scaffold conceptual understanding and negotiate collaborative tasks. Data were collected through in-depth, semi-structured, one-to-one online interviews with three Indonesian undergraduate participants, focusing specifically on their use of multiple languages during academic work and social integration processes within the university. Findings: The findings reveal that all three participants actively utilize translanguaging mixing Indonesian, Japanese, and English as a cognitive scaffolding mechanism to secure conceptual clarity and achieve epistemic access to complex disciplinary knowledge. Crucially, translanguaging functions as a pedagogical tool that enables effective collaborative meaning-making and the negotiation of academic consensus during group work. Furthermore, the practice is closely linked to greater academic confidence and the successful negotiation of their identity within the institutional environment. Conclusion: This study particularly contributes by indicating that translanguaging is a vital tool for learning that ensures academic opportunity and success in superdiverse higher education environments. It goes beyond negotiating identity to state that schools ought to officially recognize and include translanguaging practices in their curriculum and student support services. This is very important for making an environment that is genuinely welcoming to all students and helps them succeed, as well as recognizing their full linguistic and intellectual potential. Keywords: translanguaging pedagogy, english medium instruction, identity, academic equity.